Understanding variation in ambulance service non-conveyance rates: a mixed methods study - Alicia O'Cathain; Emma Knowles; Lindsey Bishop-Edwards; Joanne Coster; Annabel Crum; Richard Jacques; Cathryn James; Rod Lawson; Maggie Marsh; Rachel O'Hara; Aloysius Niroshan Siriwardena; Tony Stone; et al. (National Institute for Health Research, 2018)
Background: In England in 2015/16, ambulance services responded to nearly 11 million calls. Ambulance Quality Indicators show that half of the patients receiving a response by telephone or face to face were not conveyed to an emergency department. A total of 11% of patients received telephone advice only. A total of 38% of patients were sent an ambulance but were not conveyed to an emergency department. For the 10 large ambulance services in England, rates of calls ending in telephone advice varied between 5% and 17%. Rates of patients who were sent an ambulance but not conveyed to an emergency department varied between 23% and 51%. Overall non-conveyance rates varied between 40% and 68%. Objective: To explain variation in non-conveyance rates between ambulance services. Design: A sequential mixed methods study with five work packages. Setting: Ten of the 11 ambulance services serving > 99% of the population of England. Methods: (1) A qualitative interview study of managers and paramedics from each ambulance service, as well as ambulance commissioners (totalling 49 interviews undertaken in 2015). (2) An analysis of 1 month of routine data from each ambulance service (November 2014). (3) A qualitative study in three ambulance services with different published rates of calls ending in telephone advice (120 hours of observation and 20 interviews undertaken in 2016). (4) An analysis of routine data from one ambulance service linked to emergency department attendance, hospital admission and mortality data (6 months of 2013). (5) A substudy of non-conveyance for people calling 999 with breathing problems. Results: Interviewees in the qualitative study identified factors that they perceived to affect non-conveyance rates. Where possible, these perceptions were tested using routine data. Some variation in non-conveyance rates between ambulance services was likely to be due to differences in the way rates were calculated by individual services, particularly in relation to telephone advice. Rates for the number of patients sent an ambulance but not conveyed to an emergency department were associated with patient-level factors: age, sex, deprivation, time of call, reason for call, urgency level and skill level of attending crew. However, variation between ambulance services remained after adjustment for patient-level factors. Variation was explained by ambulance service-level factors after adjustment for patient-level factors: the percentage of calls attended by advanced paramedics [odds ratio 1.05, 95% confidence interval (CI) 1.04 to 1.07], the perception of ambulance service staff and commissioners that advanced paramedics were established and valued within the workforce of an ambulance service (odds ratio 1.84, 95% CI 1.45 to 2.33), and the perception of ambulance service staff and commissioners that senior management was risk averse regarding non-conveyance within an ambulance service (odds ratio 0.78, 95% CI 0.63 to 0.98). Limitations: Routine data from ambulance services are complex and not consistently collected or analysed by ambulance services, thus limiting the utility of comparative analyses. Conclusions: Variation in non-conveyance rates between ambulance services in England could be reduced by addressing variation in the types of paramedics attending calls, variation in how advanced paramedics are used and variation in perceptions of the risk associated with non-conveyance within ambulance service management. Linking routine ambulance data with emergency department attendance, hospital admission and mortality data for all ambulance services in the UK would allow comparison of the safety and appropriateness of their different non-conveyance rates. Funding: The National Institute for Health Research Health Services and Delivery Research programme.